Dayak Onion (Eleutherine palmifolia (L.) Merr.): Ethnomedicinal Use, Phytochemistry, Pharmacology, and Toxicology - Mulyati Sri Rahayu; Sri Wahyuni; Fury Maulina; Cut Asmaul Husna; Meutia Maulina (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2026)
Plants, plant components, and phytochemicals have long been used in disease prevention and treatment. Indonesia, known for its rich biodiversity, is the habitat of the Dayak onion (Eleutherine palmifolia (L.) Merr.), a plant species recognized for its unique characteristics. E. palmifolia is an indigenous species to Central Kalimantan, Indonesia, and has been traditionally used as a medicinal remedy for various health problems. The therapeutic benefits of E. palmifolia are attributed to its bioactive compounds including flavonoids, alkaloids, saponins, tannins, and naphthoquinones. This plant displays a variety of beneficial effects, including antioxidant, antimicrobial, anti-inflammatory, antifungal, and antidiabetic properties, and has potential as an anticancer and antiuricemic agent. Long-term use of high concentrations of this extract may lead to liver damage due to its cytotoxic properties, with toxicity increasing as the concentration of the E. palmifolia bulb extract increases. Further research is warranted to optimize these benefits, determine the optimal dosages, and establish safety guidelines. This review provides a thorough, well-structured analysis of the current advancements related to the ethnomedicinal uses, phytochemistry, pharmacology, and toxicity of E. palmifolia. These insights have the potential to facilitate the exploration of various aspects and novel treatments involving E. palmifolia in contemporary medicine. The increasing interest in these remedies has stimulated intensified research investigating diverse elements, including cultural importance, scientific validity, and risk-benefit assessments.